Multiparametric optimization of a reheated organic Rankine cycle for waste heat recovery based repowering of a degraded combined cycle gas turbine power plant. (15th February 2022) - Reshaeel, Muhammad; Javed, Adeel; Jamil, Ahmad; Ali, Majid; Mahmood, Mariam; Waqas, Adeel
Highlights: Triple cycle repowering of a combined cycle power plant by reheated organic Rankine cycle. Multiparametric optimization and comparison with organic Rankine cycle configurations. Diurnal performance analysis of triple cycle for each organic Rankine cycle configuration. Lower specific fuel and water consumption exhibited by reheated organic Rankine cycle. Abstract: The study has conducted multiparametric optimization of a newly modified double stage reheated organic Rankine cycle configuration for the objective function of specific work output and its comparison with other conventional configurations of the organic Rankine cycle for the waste heat recovery-based repowering of a degraded combined cycle gas turbine power plant using R245fa, R113, and R141b as the working fluids. Thermodynamic performance of the triple cycle formed by integrating each organic Rankine cycle configuration with the combined cycle gas turbine unit is assessed in terms of repowering, specific fuel consumption and specific water consumption along with the associated greenhouse gas emissions. 24-hour performance variation of the combined cycle gas turbine unit has been incorporated in the analysis. It is found that the double stage reheated organic Rankine cycle configuration has outperformed other configurations in terms of thermodynamic performance. Triple cycle for the double stage reheated organic Rankine cycle has resulted in an average of 1.37% increase in net power output for the working fluid R141b, equivalent to 5.10 MW of additional power output. The thermal efficiency of the triple cycle for double stage reheated organic Rankine cycle has increased by 1.40%, whereas the specific fuel consumption and specific water consumption have reduced by 1.28% and 3.35%, respectively using R141b as the working fluid. The highest waste heat recovery potential is exhibited by the integrated basic organic Rankine cycle configuration for the working fluid R245fa, recovering 30, 840 kW of waste heat, equivalent to the burning of 2467.2 kg/hr of CH4 and 6784.7 kg/hr CO2 emissions.